Regional Pro Bon Conference Held at Hilton Hotel - Watkins, Howard::::::::: (1989)
? speaking at lectern; seated: Frank D. Winston, State Senator Ken Maddy, Justice Hollis Best, Randi Saul-Olson and Glee Ewell